Answer:
(1 [tex]\frac{1}{3}[/tex], 2 [tex]\frac{1}{3}[/tex] )
Step-by-step explanation:
Given the 2 equations
7x - y = 7 → (1)
x + 2y = 6 → (2)
Multiplying (1) by 2 and adding to (2) will eliminate the y- term
14x - 2y = 14 → (3)
Add (2) and (3) term by term to eliminate y
15x = 20 ( divide both sides by 15 )
x = [tex]\frac{20}{15}[/tex] = [tex]\frac{4}{3}[/tex] = 1 [tex]\frac{1}{3}[/tex]
Substitute this value of x into either of the 2 equations and solve for y
Substituting in (2)
[tex]\frac{4}{3}[/tex] + 2y = 6
2y = 6 - [tex]\frac{4}{3}[/tex] = [tex]\frac{14}{3}[/tex] ( divide both sides by 2 )
y = [tex]\frac{7}{3}[/tex] = 2 [tex]\frac{1}{3}[/tex]